PROFILING BACHELOR OF SCIENCE IN STATISTICS (BSS) STUDENTS UNDER THE OPEN ENROLMENT POLICY - Miñoza, Susana B; Casinillo, Leomarich F (IJIET (International Journal of Indonesian Education and Teaching), 2022)
This study established a profile of Bachelor of Science in Statistics (BSS) students under the open enrolment policy of Visayas State University (VSU). The study also determined the graduation rate of the BSS students. Data on the present BSS students were collected from a survey of currently enrolled students while data on the past BSS students were taken from the previous study. Data used to track down the BSS students since their first year to determine the graduation rate of each batch covered and were taken from the Office of the University Registrar. Results showed that majority of the present BSS students are female. All BSS students surveyed come from the Visayas area with most of them come from Region VIII, Philippines. While most of the BSS students have annual family incomes below the poverty line in Region VIII, still most of them get their financial support from their parents only. Majority are regular students and want to work as statisticians in the future. The relative importance of factors influencing the choice of degree program are very similar between the past and the present BSS students. The graduation rate of BSS students is variable (coefficient of variation of 42.5%) with a median of 26.1% and a mean of 25.3%. Hence, an extensive recruitment and orientation about the program must be done to increase the enrollees and develop their interest towards the program, respectively.